Staunton, The Charter and General Ordinances of the Town of Lexington, Virginia, at 87, ch. 42, § 2 (1892) - (:unkn) unknown (My University, 1869)
If any person shall barter, give, or furnish, or cause to be bartered, given, or furnished to any minor under sixteen years of age, cigarettes, pistols, dirks, or bowie knives, having good cause to believe him or her to be a minor under sixteen years of age, shall be fined no less than ten dollars and no more than one hundred dollars
Keywords: TRANSFER - MINORS